Ionic liquids roles and perspectives in electrolyte for dye-sensitized solar cells - Talip, R.A.A. (MDPI, 2020)
Exploration of renewable energy, such as solar energy, is imminent not only to cater to the escalating energy demand but also to address the uprising environmental issues due to heavy usage of non-renewable fossil fuel. The dye-sensitized solar cells (DSSCs) which are considered as the third-generation solar cells, have a huge potential to be commercialized due to their low cost, simplicity in fabrication, and promising photon-to-electrical energy conversion efficiency. Nevertheless, a high cell efficiency can only be achieved when an organic solvent is incorporated into the formulation of the electrolyte, which is prone to evaporation and leakage. As a result, DSSCs become unsuitable for long-run usage due to thermal instability in the electrolyte. The early intention of incorporating ionic liquids (ILs) into the electrolyte was to curb the abovementioned problem and to enable the DSSCs to function as a sustainable energy device. As such, this article briefly reviews how ILs have been incorporated into the electrolyte formulation and the extent of how the ILs can affect the cell efficiency in various electrolyte states. The role of the ILs in a range of electrolytes is also highlighted. This sheds light on the true purpose of introducing ILs into DSSC electrolyte, which is to enhance the ionicity of the electrolyte. Â© 2020 by the authors.